Cathodal tDCS of the bilateral anterior temporal lobes facilitates semantically-driven verbal fluency. (March 2018) - Binney, Richard J.; Zuckerman, Bonnie M.; Waller, Hilary N.; Hung, Jinyi; Ashaie, Sameer A.; Reilly, Jamie
Abstract: In a verbal fluency task, a person is required to produce as many exemplars of a given category (e.g., 'animals', or words starting with 'f') as possible within a fixed duration. Successful verbal fluency performance relies both on the depth of search within semantic/phonological neighborhoods ('clustering') and the ability to flexibly disengage between exhausted clusters ('switching'). Convergent evidence from functional imaging and neuropsychology suggests that cluster-switch behaviors engage dissociable brain regions. Switching has been linked to a frontoparietal network dedicated to executive functioning and controlled lexical retrieval, whereas clustering is more commonly associated with temporal lobe regions dedicated to semantic and phonological processing. Here we attempted to modulate cluster-switch dynamics among neurotypical adults (N = 24) using transcranial direct current stimulation (tDCS) delivered at three sites: a) anterior temporal cortex; b) frontal cortex; and c) temporoparietal cortex. Participants completed letter-guided and semantic category verbal fluency tasks pre/post stimulation. Cathodal stimulation of anterior temporal cortex facilitated the total number of words generated and the number of words generated within clusters during semantic category verbal fluency. These neuromodulatory effects were specific to stimulation of the one anatomical site. Our findings highlight the role of the anterior temporal lobes in representing semantic category structure and support the claim that clustering and switching behaviors have distinct substrates. We discuss implications both for theory and application to neurorehabilitation. Highlights: Evaluated the effect of tDCS delivered at three distinct sites on verbal fluency. Anterior temporal tDCS facilitated output during semantic category fluency. Data suggests the effect is site and task-specific. Suggests anterior temporal lobe represents semantic category structure. Practical implications for application of tDCS to neurorehabilitation.